The Effect of Tourists' Motivations on Cognitive, Affective, and Unique Image of Bali - Alita Prameswari; Christina Rahardja Honantha; Dudi Anandya (Journal of Management and Business, 2020)
This research examines the effect of tourists’ motivations on cognitive, affective and unique image of Bali. The model used for this study adopted from Llodra-Riere, et al. (2015).  The variable of the study consists of information source, motivation, cognitive image, affective image and unique image. The model in this study used six hypotheses. This research is quantitative and causal type research. This study used non-probability and purposive sampling approach, sample characteristics are the Surabaya tourists who had experience in using information sources from internet platform and other information sources which is non-internet platform that been collected information before visiting Bali and have visited Bali at least once in the past one year. The data is obtained from questionnaire that is distributed to 310 respondents and analyze using Structural Equation Modeling (SEM), with SPSS 18 and LISREL 8.8 for measurement and structural model. The result shows that motivation did not influence affective image of Bali. There are five hypotheses are significant. Information sources influence motivation; cognitive image and unique image influence affective image; motivation influences cognitive image and unique image of Bali. The benefit of this research can help tourism industry in Bali to improve their marketing communication by using social media, website platform and online advertisement.